Can the Pfannenstiel skin incision length be adjusted according to the fetal head during elective cesarean delivery? - Kaya, Baris; Ozay, Ozlen Emekci; Ozay, Ali Cenk; Tüten, Abdullah (Frontiers in Surgery, 2023)
Objective The study aims to determine whether the Pfannenstiel skin incision can be adjusted according to the fetal head's occipitofrontal diameter (OFD) during primary cesarean delivery (CD). Background Eligible 114 nulliparous women delivered at term by cesarean section in which Pfannenstiel skin incision was performed according to the occipitofrontal diameter (OFD) of the fetal head between June 2017 and September 2021 were included. Non-vertex presentations, all emergency cesarean sections, severe preeclampsia, women in an active phase of the first stage of labor and second stage of labor, Placenta Previa and low-lying placenta, multiple pregnancies, and uncontrolled gestational diabetes mellitus were excluded. Results Among 114 eligible nulliparous women, the mean OFD was 116,1±7,2 (99-138 mm), and the measurement of the Pfannenstiel skin incision length, which was performed according to the OFD was found as 122,8±9,2 (100-155) The difference between OFD and Pfannenstiel incision kept remained within 10 mm in 90 (%82.5,2), 10-20 mm in 17 (15.5 %) and more than 20 mm in two women (1.8 %), respectively. This technique was successful in 109 (95.6%) out of 114 women without extending the skin incision. In five women, skin incision needed to be extended up to 38 mm. In ten women (8.7 %), the rectus abdominus muscle was cut partially to deliver the fetal head. The mean fetal umbilical artery ph was 7,33 ± 0.05. No neonatal hypoxia was encountered in the study. Conclusion Pfannenstiel skin incision can be adjusted according to the OFD with minimal margins of error. This technique may provide better cosmetic results by avoiding unnecessarily prolonged incisions with similar newborn outcomes. Trial registration The study was retrospectively registered on 01/12/2022 with the registry number (NCT05632796). e